Pengaruh Penggunaan Media Pembelajaran Aplikasi Canva Terhadap Kreatifitas dan Hasil Belajar Siswa pada Mata Pelajaran IPS Kelas VIII di SMP Muhammadiyah 2 Purwokerto - Yuni Prihartini; Sriyanto Sriyanto (Proceedings Series on Social Sciences & Humanities, 2023)
The background of this research was to determine the influence of the use of learning support media in the form of Canva-based media on creativity and student learning outcomes in social studies subjects. Research objectives: 1) analysis of the effect of using Canva media in learning on the learning creativity of 8th grade students in Social Sciences subjects. 2) analysis of the effect of using Canva media in learning on student learning outcomes in class 8 social studies subjects. 3) analysis of the influence of the use of Canva media in learning on creativity and learning outcomes of class 8 social studies students. This is a quantitative experiment with a population of SMP Muhammadiyah 2 Purwokerto students and a sample of 40 grade 8 students. The research utilized the True Experimental Design. Data collection through several instruments namely questionnaires, tests, and observations. By utilizing the SPSS version 21 application, the Man Whitney test, normality test, and Wilcoxon test were also carried out. The results of the study show that the students' scores before and after using Canva media as a social science learning medium are different. Judging from the significant value of learning creativity tcount -3.285 > ttable 2.000 or tcount 3.285 > ttable 2.000 at a significant level of 5%. If tcount is greater than ttable then Ho is rejected and Ha is accepted, meaning that Canva media has an influence on increasing student learning creativity. Another positive impact can also be seen from the increased student learning outcomes as evidenced by the significant value of tcount -5.246 > ttable -2.000 or tcount 5.246 > ttable 2.000 at a significant level of 5%, it can be concluded that if tcount is greater than ttable then Ho is rejected and Ha is accepted This means that Canva media has an influence on increasing student learning outcomes. The use of Canva-based learning media affects learning outcomes, as the results of the Man Whitney test show the Asymp value. So it was concluded that the use of Canva learning media had an effect on increasing the creativity and learning outcomes of Class 8 students in Social Sciences at SMP Muhammadiyah 2 Purwokerto.